Persistence in treatment for one year among patients in Nigeria with first-episode of Schizophrenia (2014)
Objective: The aim of this study was to examine the magnitude of poor persistence in treatment among patients with schizophrenia and to identify associated factors. Methods: All eligible patients (N5216) seen at the University College Hospital in Ibadan, Nigeria, over a five-year period were retrospectively followed up until the time of their last visit. Time to first default was examined by Kaplan-Meier survival analyses. Alog-rank test was used to compare survival times for different variables. The contribution of the variables that affected time to default was examined by Cox regression analysis. Results: Only 24% of the sample remained in treatment at the one-year follow-up. Persistence as measured by mean6SE time to all-cause treatment default was 17.8061 .44 weeks. Of several variables examined, including whether patients were taking first- or second-generation antipsychotics, none were found to predict persistence. Conclusions: Persistence in treatment of patients with a first episode of schizophrenia was low.